Case Study Summary: Horticulture Exports from Kenya: Are Horticultural Exports a Replicable Success Story? Evidence from Kenya and Cote d'voire - Ngigi, Margaret; Minot, Nicholas (NEPAD, 2005)
Conference Paper No. 14